Implementasi Standarisasi Pengolahan Tanaman Obat Menjadi Jamu Tradisional sebagai Rintisan Usaha Warung Jamu Berbasis Komunitas Lokal di Desa Bajo Kabupaten Blora - Zainuri Iksan; Wihatmoko Waskitoaji (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance community competence in processing local medicinal plants into traditional herbal drinks (jamu) that are safe, hygienic, and economically valuable, while simultaneously establishing a community-based herbal beverage enterprise to strengthen the local economy. A participatory approach was implemented through technical training, hands-on practice in processing medicinal plants, business management mentoring, and the establishment of a simple community business unit. The program partner was the Herbal Farmer Group “Bina Alamsri” in Bajo Village, Blora Regency, involving 30 community members. Evaluation was conducted using pre- and post-test questionnaires, interviews, and documentation, and the data were analyzed descriptively using quantitative pre-post comparison techniques. The results of this community service program demonstrated a significant improvement in participants’ knowledge and skills related to the standardized and hygienic processing of medicinal plants. In addition, the program successfully established a community enterprise through a jamu stall with a production capacity of 200–300 bottles per month, providing additional income for group members and creating opportunities for sustainable business development based on local potential.